Self determination and quality of life: a comparison of the measurement scales for people with disabilities - Zappella, Emanuela (Formazione & insegnamento, 2019)
Self-determination is a key concept to promote greater self-awareness in the subjects with disability, to build appropriate educational or professional projects and to evaluate the already active programs. The objective of this work is the analysis of the evaluation scales that, starting from the different models, measure self-determination with particular reference to: recipients, areas, items and data collection methods. The article closes with a reflection on the possibility of constructing a scale that considers all the aspects of selfdetermination offered in the literature and collects the opinion of all the subjects involved in self-determination projects.